Digest: Ecological crossover effects on sexual selection*. (21st September 2018) - Ershova, Natalia
Abstract: Environmental conditions during birds' nonbreeding season can affect the manifestation of secondary sexual traits and therefore sexual selection. In pied flycatchers, the size of the wing patch is a secondary sexual trait that signals mate value and is influenced by the previous winter's conditions. Female preference changes accordingly with the conditions of the previous nonbreeding season.